The Effect Of Organizational Commitment On Turnover Intention With Job Satisfaction As A Mediation Variable In PT Darma Jaya Valuta Gianyar - Ni Kadek Diantini Putri; Gde Bayu Surya Parwita; Tiara Carina (LPPM Universitas Sains dan Teknologi Komputer, 2026)
Turnover intentionis the tendency or degree to which an employee is likely to leave the company either voluntarily or involuntarily due to the lack of attractiveness of the current job and the availability of other job options. This study aims to determine the effect of organizational commitment on turnover intention with job satisfaction as a mediating variable at PT Darma Jaya Valuta Gianyar. This research was conducted at the head office and branch offices of PT Darma Jaya Valuta Gianyar. The sample in this study was 32 employees of PT Darma Jaya Valuta Gianyar. The sampling technique in this study was saturated sampling, and data collection was carried out through documentation, interviews, and questionnaires. The data analysis technique used in this study was a variance-based structural equation model or component-based structural equation model through the SmartPLS 4.0 program. Based on the results of the analysis, this study shows that organizational commitment has a positive and significant effect on job satisfaction. Organizational commitment has a negative and significant effect on turnover intention. Job satisfaction has a negative and significant effect on turnover intention. Job satisfaction can be a mediating variable in the influence of organizational commitment on turnover intention.